Interdependência entre estrutura atômica e eletrônica de grafeno multicamada e isolantes topológicos - Paula Mariel Coelho Neto (2015)
The structural and electronical properties of two materials with interesting bidimensional behavior were studied in this work: Multilayer Epitaxial Graphene and a topological insulator (Bi2Te3). Identification of the two-dimensional behavior of graphene was held by several techniques, among them, X-ray diffraction (XRD), Raman spectroscopy and Near Edge X-ray Absorption Fine Structure (NEXAFS). We studied three different samples grown by heating of a SiC substrate for different times to establish a relationship between the time of growth and graphene-like or graphite-like behaviour. Comparing the absorption profiles of these samples, we see that the sample of 45 minutes presents an intermediate profile to the others. We observe and justify the existence of an image potential state for sample of 60 minutes. Hence, we can treat it as a state of the Graphene. Our second study of interest started with the observation of different atomic levels of the sample of Bi2Te3 using Scanning Tunneling Microscopy (STM). A theoretical study was performed to explain the electronic structure of the topological insulator and simulate possible stable atomic terminations. The sample was also characterized by X-ray diffraction at the National Laboratory of Synchrotron Light at the XRD2 beam. Data was analyzed and compared to theoretical models. Through our studies, we demonstrate that a Bismuth bilayer emerges as a second stable state upon the sample of five monolayers of Bi2Te3, behaving like a two-dimensional classical electron gas. The growth of this bilayer is accomplished through the submission of the sample at high temperatures but, once we obtain this configuration, the state becomes stable at room temperature.